An experimental study of conversion of carbon dioxide into hydrocarbon fuel by using photocatalytic method - Mohamad Redzuan, Bujang (2010)
The production of hydrocarbon fuel, methanol (CH3OH) from the carbon dioxide (CO2) has been studied using photosynthesis method. The study conducted in FKKSA lab using existing reactor and modified with addition of photosynthesis lamp. The effect of catalyst influenced the yield of the CH3OH for the sample. With the presence of a metal oxide catalyst, overall water splitting can be driven by visible light to produce hydrogen and oxygen. After the hydrogen and oxygen splitting process, hydrogen reacts with carbon dioxide to produce hydrocarbon fuel synthetically. The sample obtain from the reaction been tested to define the composition. The functional groups of the product which is CH3OH are identified by using fourier transform infrared spectrometer (FTIR). From the studies showed that the photocatalytic method that has been use is applicable but need more of enhancement to produce high yield of CH3OH which can be commercialized.